2015
DOI: 10.1093/jisesa/iev051
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy is Effective in Protecting Honeybee Larvae from American Foulbrood Disease

Abstract: American foulbrood disease has a major impact on honeybees (Apis melifera) worldwide. It is caused by a Gram-positive, spore-forming bacterium, Paenibacillus larvae. The disease can only affect larval honeybees, and the bacterial endospores are the infective unit of the disease. Antibiotics are not sufficient to combat the disease due to increasing resistance among P. larvae strains. Because of the durability and virulence of P. larvae endospores, infections spread rapidly, and beekeepers are often forced to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
17
1
2
Order By: Relevance
“…P. larvae phages have been isolated and sequenced in Portugal [ 14 ], Germany [ 15 ], and the United States [ 16 , 17 , 18 , 19 , 20 , 21 ], with the latter accounting for the vast majority of published genomes. In addition, six studies have been published within the last two years on treating AFB with P. larvae phages or P. larvae phage endolysins [ 15 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. larvae phages have been isolated and sequenced in Portugal [ 14 ], Germany [ 15 ], and the United States [ 16 , 17 , 18 , 19 , 20 , 21 ], with the latter accounting for the vast majority of published genomes. In addition, six studies have been published within the last two years on treating AFB with P. larvae phages or P. larvae phage endolysins [ 15 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, injection of environmentally derived Pseudomonas aeruginosa phage increased survival time of P. aeruginosa -infected D. melanogaster [61]. In addition to these laboratory-induced infections, oral delivery of a phage preparation has been reported to suppress the impact of American foulbrood disease caused by Paenibacillus larvae in hives of the honeybee, Apis mellifera [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Temperate phages, especially those capable of transferring antibiotic resistance genes, are not safe and should be excluded from phage therapies. However, there are data suggesting that temperate phages could potentially find use in therapy ( Chung et al, 2012 ; Meader et al, 2013 ), especially in the fight against AFB, as presented by Ghorbani-Nezami et al (2015) . Of course, for safety reasons, their application should be carefully considered.…”
Section: P Larvae Bacteriophages and Their Characteristicsmentioning
confidence: 99%
“…Available studies indicated a possible protective effect for bees infected with these extremely resistant forms of bacteria. The aforementioned effect of three P. larvae phages F, WA and XIII was studied in vivo by Ghorbani-Nezami et al (2015) on larvae infected with NRRL B-3650 spores. The authors observed that the survival of larvae treated with phages (phage-treated control) as well as healthy larvae (negative control) was comparable and phages did not cause any deleterious effects.…”
Section: Phage Application Potentialmentioning
confidence: 99%